Taxonomic study on the planthopper genus Macrocixius Matsumura (Hemiptera: Fulgoromorpha: Cixiidae) with descriptions of two new species from China - Zhang, Pei; Chen, Xiang-Sheng (Zootaxa, 2013)
The cixiid planthopper genus Macrocixius Matsumura, 1914 (Hemiptera: Fulgoromorpha: Cixiidae: Cixiini) is known to from two species: M. giganteus Matsumura, 1914 and M. grossus Tsaur & Hsu, 1991 which are redescribed and illustrated. Two new species, M. rarimaculatus sp. nov. and M. unispinus sp. nov. from south China, are described and illustrated. The generic characteristics are redefined and a key to the species is provided.